1991
DOI: 10.1128/mcb.11.5.2785
|View full text |Cite
|
Sign up to set email alerts
|

Ras GTPase-activating protein physically associates with mitogenically active phospholipids.

Abstract: The physical interaction between GTPase-activating protein (GAP) and lipids has been characterized by two separate analyses. First, bacterially synthesized GAP molecules were found to associate with detergent-mixed micelles containing arachidonic but not with those containing arachidic acid. This association was detected by a faster elution time during molecular exclusion chromatography. Second, GAP molecules within a crude cellular lysate were specifically retained by a column on which certain lipids had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Because CREB/ ATF-1 mediate cAMP-response element-dependent gene expression, one possible mechanism by which p38 MAPK is involved in thrombin-induced growth in VSMC is via activation of iPLA 2 , thereby releasing arachidonic acid, which in turn stimulates ATF-1-dependent gene expression. Previous work from other laboratories showed that arachidonic acid and its eicosanoid metabolites are involved in the mediation of mitogenic signaling events such as formation of focal adhesions (43)(44)(45)(46). Because both cPLA 2 and iPLA 2 appear to be involved in agonist-induced arachidonic acid release (11, 20, 23-25, 29, 30) and a role for both PLA 2 s has been demonstrated in the regulation of cell growth (27,28,31), it would be interesting to learn which of these PLA 2 s is involved in receptor tyrosine kinase and G protein-coupled receptor agonist-induced focal adhesion formations.…”
Section: Resultsmentioning
confidence: 99%
“…Because CREB/ ATF-1 mediate cAMP-response element-dependent gene expression, one possible mechanism by which p38 MAPK is involved in thrombin-induced growth in VSMC is via activation of iPLA 2 , thereby releasing arachidonic acid, which in turn stimulates ATF-1-dependent gene expression. Previous work from other laboratories showed that arachidonic acid and its eicosanoid metabolites are involved in the mediation of mitogenic signaling events such as formation of focal adhesions (43)(44)(45)(46). Because both cPLA 2 and iPLA 2 appear to be involved in agonist-induced arachidonic acid release (11, 20, 23-25, 29, 30) and a role for both PLA 2 s has been demonstrated in the regulation of cell growth (27,28,31), it would be interesting to learn which of these PLA 2 s is involved in receptor tyrosine kinase and G protein-coupled receptor agonist-induced focal adhesion formations.…”
Section: Resultsmentioning
confidence: 99%
“…5-LOX products of arachidonic acid such as leukotriene C 4 have also been shown to mediate epidermal growth factor-induced cytoskeletal rearrangement (9). The findings that eicosanoids, particularly the LOX products of arachidonic acid, mediate mitogen-induced signaling events via inhibition of GTPase activating proteins offer additional support for their role in cell growth (11,12,49). In addition to their role in the mitogenic signaling events cited above, some eicosanoids such as prostaglandin F 2␣ and 12(R)-hydroxy-5,8,14-eicosatrienoic acid induce the expression of angiogenic factors bFGF-2 and VEGF in rat aortic smooth muscle cells and rabbit limbal microvessel endothelial cells, respectively (50,51).…”
Section: (S)-hete Stimulates Autocrine Growth In Hmvecmentioning
confidence: 99%
“…Arachidonic acid and its metabolites, known as eicosanoids, are involved in the regulation of a variety of biological processes including vascular tone (5,6). In addition, these lipid molecules have been reported to mediate intracellular signaling events in response to a number of stimuli (7)(8)(9)(10)(11)(12). A large body of pharmacological data suggests that arachidonic acid and its eicosanoid metabolites stimulate mitogenesis in various cell types, including cancer cells (13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…There are numerous reports of PA effects on protein kinases such as the PKC (138,173,280), protein kinase N, and p21 cdcrac families (126,129,167,267,281). PA also appears to have inhibitory effects on Ras-GTPase-activating proteins (252) and Rho-GTP-dissociating isoforms (37; reviewed in Refs. 19,115,126,155).…”
Section: As Indicated In Substrates Formentioning
confidence: 99%